MELEMBAGAKAN INDIKATOR INTERAKSI KEPENDUDUKAN, LINGKUNGAN HIDUP, DAN PEMBANGUNAN - Sofian Effendi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1993)
Increasing concern on the problemof carrying in broad sense (natural, social, and built environment) which support to the process of sustainable development has stimulated awareness on how important it is for the government and the community to maintainthe development and environment in the perfect harmony.This paper discuss varions attempt in developing new policy indicators needed by the government to monitor the performance of sustainable development. These efforts are that the policy making should always be provided with qualities, environment, development strategies, and its related interactions.